Letters to God a novel - Doughtie, Patrick; Perry, John (Zonderkidz, 2010)
Tyler writes a letter asking God to help him find the compass he has misplaced, but on his way to send it he meets others who could use some help and adds a series of postscripts. Includes a biography of the real Tyler and instructions on writing your own letter to God.